(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2007)
This short notes deals with the re-description and re-illustration of the holotypes of Thalmanninella brotzeni Sigal, 1948 and Rotalipora globotruncanoides Sigal, 1948, from Sidi Aissa, Algeria, middle Cenomanian. Both species are attributed to the genus Thalmanninella.